Tales from a not-so-fabulous life - Russell, Rachel Renee (New York : Aladdin, 2009)
Fourteen-year-old Nikki Maxwell writes and sketches in her diary about her struggle to be popular at her exclusive new private school, and about giving up on being part of the elite group, before figuring out a way to simply be herself.
Horn Book, October 2009
Kirkus Review, May 2009
5.8
3-6
3-6.
Horn Book
Keywords: Popularity -- Juvenile fiction; Friendship -- Juvenile fiction; Artists -- Juvenile fiction; Schools -- Juvenile fiction; Popularity -- Fiction; Friendship -- Fiction; Artists -- Fiction; Schools -- Fiction; Diaries -- Fiction; Popularity -- Fiction; Friendship -- Fiction; Artists -- Fiction; School stories; Diaries -- Fiction; Diary fiction